Isolation of kistomin milk coagulant from calloselasma rhodostoma venom - Amira Alia, Zulkifli (2020)
Rennet is an enzyme used in the milk clotting process for cheese production. Rennet is produced in the stomach of ruminant mammal especially calf. However, increasing demand for cheese with ongoing research for innovative cheese products has encouraged the researchers to explore the other new sources of milk clotting protease. The new sources of milk clotting protease include animal, plant, microbes and fungi have been investigated. Snake venom contains a rich and good source of protease that needs to be explored as well for its potential in milk clotting. The objectives of this study were to screen eleven different species of snake venoms, to isolate the protease enzyme from the most potential venom capable to coagulate milk using chromatography techniques, to determine the enzymes milk clotting parameters and compare with a commercial milk clotting protease. The results revealed that a crude venom from Calloselasma rhodostoma showed the fastest clotting time that is 2.83±0.17 minutes and was chosen for further purification process. The milk clotting enzyme was purified by HiTrap SP FF ionexchange chromatography and further separated using HiPrep 26/60 Sephacryl S 200 HR size exclusion column. It was purified 4.41±0.06 fold and exhibited recovery activity of 54.34 %. SDS-PAGE analysis indicated a single band with a molecular mass of approximately 26 kDa. The purified protease was completely inhibited by EDTA and 1,10 phenanthroline revealing to be a metalloprotease SVMPs P-I Kistomin confirmed by Mass Spectrometry analysis. The specific activity of kistomin is 62.20 (U/mg). The milk clotting activity (MCA) of kistomin under optimum conditions, was 810.44±42.45 (SU/mL) and the PA of kistomin was 1.39±0.01 (U/mL), resulted in high ratio of MCA/PA value of 585.05. The clotting activity of kistomin on milk was the highest at 0.76 mg/mL kistomin concentration, 8 % (w/v) of calcium chloride concentration, temperature of 48 °C and stable over wide range of pH 5-7 with the peak of pH 6.5. The addition of Ba2+, Mn2+and Ca2+ions as cofactor significantly increased the enzyme activity but inhibited by Hg2+, Pb2+and Fe2+ions. The Km value of kistomin on casein is 1.153±0.08 mg/mL. The low Km value of kistomin on casein showed it has high affinity to casein. Kistomin promoted extensive cleavage of kappa casein and low level of beta casein hydrolysis. From this preliminary study, it can be concluded that kistomin has potential to be a coagulant in the dairy industry. However, due to the source of the protease being from a snake and always been considered lethal by people in general, a thorough safety investigation warranted before been utilised in any industry.